One-punch man. 04 - ONE, 1986- (Shonen Jump manga., 2016)
Saitama is now a certified hero! And with that title comes great responsibility-he's required to perform one heroic deed per week. While Saitama makes the rounds to meet his quota, an incoming threat from outer space is screeching toward Earth...